Gender differences in Iceland's education system - Gylfason, Gísli; Zoega, Gylfi (Menntavísindasvið Háskóla Íslands, 2022)
This paper describes and compares the performance of boys and girls in the Icelandic education system.The study of gender differences in schools has a long history. An extensive and interesting survey edited by William Hadow in the U.K. in 1923 examined existing evidence from the perspective of medicine, psychology and education studies. The authors found that intra-gender variation in abilities was greater than gender differences. Nevertheless, notable gender differences had to do with girls being more obedient, industrious and respectful while boys were more independent and harder to manage. Recent research in the field of education studies has confirmed many of these differences.In recent decades, the apparent educational underperformance of boys in the Western world has received increased attention. Several books, some of which are controversial, have been written on this topic (such as Kindlon & Thompson, 2000; Palmer, 2009; Sax, 2016; Sommers, 2001). This paper surveys research on gender imbalance in education, which covers the effect of boys having lower non-cognitive skills; boys having a different set of values and attitudes and not valuing educational performance as much as girls; the importance of family background in shaping boys’ attitudes towards education; and teachers viewing boys as being lazier and girls more conscientious.We then use data on comprehensive examinations in 4th, 7th and 10th grade for two cohorts in Iceland. We find that there is no statistically significant difference between the mean grade of boys and girls in mathematics but a significant and sizeable difference in the mean grade in Icelandic, which exists in 4th grade and then becomes larger in 7th grade and in 10th grade. However, the intra-gender variation is much greater than the differences in mean grade. We then look at the tails of the distribution and find that a large majority of those with the 10% lowest grades in Icelandic were boys and a minority of those with the 10% highest grades. The gender differences are ...